Inhaled dry powder apomorphine (VR040) for 'off ' periods in Parkinson's disease: an in‐clinic double‐blind dose ranging study. (26th March 2013) - Grosset, K. A.; Malek, N.; Morgan, F.; Grosset, D. G.
<x xml:space="preserve">Abstract</x> Background 'Off' periods increase as Parkinson's disease (PD) progresses and the benefits of standard therapy wane. Subcutaneous apomorphine rescues 'off' periods, but patient self‐injection and adverse cutaneous effects are sometimes problematic. Methods We assessed safety, tolerability and efficacy of inhaled dry powder apomorphine (VR040) in a double‐blind clinic‐based Phase II study. Of 48 patients recruited at nine sites, 47 were randomized 2:1 inhaled apomorphine/placebo. Respirable doses (drug predicted to reach the lung), ascending through 1.5, 2.3, 3.0 and 4.0 mg until efficacy was achieved, were administered to patients in a practically defined 'off' state. The primary endpoint was the response in unified PD rating scale Part 3 (UPDRS 3), at the highest dose received by the patient. Secondary endpoints included time to 'on', the proportion of patients converting from 'off' to 'on', and duration of 'on'. Results In the 47 intent‐to‐treat patients with PD, mean age 60.6 years, the mean UPDRS 3 improvement was significantly greater for VR040 at 26.8 points (standard deviation 12.0), vs 14.9 (16.3) for placebo (treatment difference 11.6, 95% confidence interval 2.3–20.9, P = 0.016). Rapid apomorphine absorption (2–7 min) translated to rapid (mean 10 min) reversal from the 'off' state. Adverse effects did not differ between VR040 and placebo; no patient discontinued due to an adverse event; one serious adverse event (constipation) in the VR040 group was considered unrelated to trial medication. Conclusions Inhaled apomorphine shows significant promise as a replacement for intermittent subcutaneous injections; further studies are appropriate to optimize efficacy and tolerability.